2019
DOI: 10.1021/acs.biochem.9b00107
|View full text |Cite
|
Sign up to set email alerts
|

Crossing the First Threshold: New Insights into the Influence of the Chemical Structure of Anionic Porphyrins on Plant Cell Wall Interactions and Photodynamic Cell Death Induction

Abstract: In this study, our fundamental research interest was to understand how negatively charged porphyrins could interact with a plant cell wall and further act inside cells. Thus, three anionic porphyrins differing in their anionic external groups (carboxylates, sulfonates, and phosphonates) were tested. First, the tobacco cell wall was isolated to monitor in vitro its interactions with the three different anionic porphyrins. Unexpectedly, these negatively charged molecules were able to bind to the negatively charg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…According to the phenotypical effects observed in TPPS-treated mycelium under light, it was of interest to localize TPPS inside the cells. In tobacco plant cells, TPPS was also tested at 3.5 µM and it was the most effective porphyrin PS to induce cell death under a short light period of 5 hours and it was proven to mainly localize in the cell wall (Riou et al 2014;Issawi et al 2019). Thus, a similar localization of TPPS was expected in the fungal cells.…”
Section: Tpps Localization Inside Mycelial Cellsmentioning
confidence: 89%
See 3 more Smart Citations
“…According to the phenotypical effects observed in TPPS-treated mycelium under light, it was of interest to localize TPPS inside the cells. In tobacco plant cells, TPPS was also tested at 3.5 µM and it was the most effective porphyrin PS to induce cell death under a short light period of 5 hours and it was proven to mainly localize in the cell wall (Riou et al 2014;Issawi et al 2019). Thus, a similar localization of TPPS was expected in the fungal cells.…”
Section: Tpps Localization Inside Mycelial Cellsmentioning
confidence: 89%
“…Indeed, TPPS with an ammonium counterion could be as an excellent antifungal candidate. Moreover, it was demonstrated that TPPS remains negatively charged in a large array of chemical environments, even under acidic pH and does not aggregate in media, allowing it to diffuse through cell walls and membranes more easily (Leroy-Lhez et al 2019;Issawi et al 2019). Therefore, this PS was thought as an excellent candidate for APDT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With the aim to develop APDT for agriculture applications, TPPS could be a good candidate because of its low toxicity for plants. Moreover, TPPS remains negatively charged in many chemical environments even under acidic pH and does not aggregate in solution, allowing it to easily permeate cells through cell walls and membranes 29,30 . Therefore, we hypothesized that TPPS could be a good PS candidate to kill the plant pathogen B. cinerea and has potential to be a safe option for grapevine (Vitis vinifera L.) explants.…”
mentioning
confidence: 99%